Technological Progress and Cultural Change in Sharia Insurance: Impact and Challenges - Shofya Humaira Siti Salma; Tajul Arifin; Abdal Abdal (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The aim of the research is to find out how the impact and challenges of technological advances and cultural changes in Islamic insurance. This is because this paradigm shift not only affects the operations of insurance companies, but also permeates cultural elements in the industry. The researcher used a qualitative methodology. The data collection technique is sourced from books, related journals and the internet. The analysis method used was descriptive analysis. The results of his research state that technological advances, such as the use of artificial intelligence, big data, have shaped a new landscape in risk management and insurance services. Meanwhile, cultural changes in society also affect consumer preferences and norms surrounding Islamic insurance. In terms of impact, the increase in operational efficiency, personalization of services, and product innovations that arise thanks to the latest technology or in general the impact is becoming efficient, personalized, scalable and agile. However, challenges such as lack of capital, lack of professional human resources, cyber security risks, evolving regulations, and adaptation to cultural changes